Endearing epistles from a Dutch Colonial Governor to a Malay ruler and a Malay ruler to a Dutch Colonial Governor: a comparison - Musa, Hashim; Abdul Aziz, Adi Yasran; Che Rodi, Rozita; Noor Muhammad, Salmah Jan (Faculty of Modern Languages and Communication, University of Putra, 2013)
In this paper two letters will be studied, one from a Dutch Colonial Governor to the ruler of Sambas dated 1848 and the other from Sultan Ahmad Ibn Sultan Zain Al-‘Abidin of Terengganu to Genderal Baron van der Capellen in Betawi (Jakarta) dated 1824. The studies are in the forms of transliteration and annotation of the letters and also a general discussion of the historical background and content of the letters. Discussion on the common features of the two letters will be made, namely the writing of a short formulaic heading on top of the page as a kind of statement, kind words of endearment and honorable words of addressing the recipients, prayer to the Almighty for the long life and good health of the addressee and the mention of the exchange of precious gifts. One feature that is in complete contrast with the etiquette of Malay rulers’ letter writing was the conspicuous introduction in the opening line of the Governor-General’s letter, of the status of the sender with grandeurs mentions of one’s honor and awards, and also the use of plain paper without illumination by the Dutch Governor-General. These were in complete contrast to the Malay rulers’ letter writing style of a simple mention of the status of the ruler and the using of intricate illumination. This study also revealed that although the letter from a Dutch colonial Governor-General was to one of the Malay rulers in his dominions, the civility, mutual respect and appropriate decorum of addressing between rulers, were practiced and adopted.